Response and training needs of school staff towards students self-injury - Berger, E.; Hasking, Penelope; Reupert, A. (Elsevier Science Ltd., 2014)
Although school staff are in a prime position to intervene with students who self-injure, how they respond to these students and their training needs regarding self-injury have not been examined. The aims of this study were to explore the responses and training needs of school staff towards youth self-injury. Pre- and in-service teachers and other school staff (N = 768) completed open-ended questions. Results suggested that school staff require training to respond effectively and confidently to students who self-injure. Self-injury education programs may enhance the knowledge and confidence of staff to detect and respond to students who self-injure.